2001
DOI: 10.1186/1471-2180-1-2
|View full text |Cite
|
Sign up to set email alerts
|

A tandem repeats database for bacterial genomes: application to the genotyping of Yersinia pestis and Bacillus anthracis

Abstract: BackgroundSome pathogenic bacteria are genetically very homogeneous, making strain discrimination difficult. In the last few years, tandem repeats have been increasingly recognized as markers of choice for genotyping a number of pathogens. The rapid evolution of these structures appears to contribute to the phenotypic flexibility of pathogens. The availability of whole-genome sequences has opened the way to the systematic evaluation of tandem repeats diversity and application to epidemiological studies.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(66 citation statements)
references
References 25 publications
1
63
0
2
Order By: Relevance
“…All the repeat units at the different loci contained point mutations, and small insertions and deletions; this phenomenon was first described in the minisatellite in the human insulin gene, and has since been shown to be the case in all VNTR loci described, both eukaryotic and prokaryotic (Mazars et al, 2001;Owerbach & Aagaard, 1984). Like the VNTRs described in other bacterial genomes, and unlike those in eukaryotes, the repeat units in S. aureus are not G+C rich (Le Fleche et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…All the repeat units at the different loci contained point mutations, and small insertions and deletions; this phenomenon was first described in the minisatellite in the human insulin gene, and has since been shown to be the case in all VNTR loci described, both eukaryotic and prokaryotic (Mazars et al, 2001;Owerbach & Aagaard, 1984). Like the VNTRs described in other bacterial genomes, and unlike those in eukaryotes, the repeat units in S. aureus are not G+C rich (Le Fleche et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Typing of repetitive DNA markers, such as SSRs, is invaluable in genotyping organisms with limited genetic diversity (1,23). However, inherent problems in sequencing mononucleotide repeats limit its application, as Sanger sequencing often fails to resolve poly(G) repeats exceeding 11 bp (10,15).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned previously, data from early work in GAS suggested that PCR/CRISPR array size correlated with RFLP typing results (66). Following this work, Vergnaud and colleagues used the YPa (Yp1) locus as a VNTR marker for MLVA in Y. pestis (33,90). More recently, using both outbreak and control isolates, two groups have shown that "CRISPR size typing" can be successfully implemented in Salmonella serovar Typhimurium and Salmonella serovar Newport (49,69).…”
Section: Subtyping Based On Crispr Locus Sizementioning
confidence: 99%